Photochemistry and Transport of Carbon Monoxide in the Middle Atmosphere - Solomon, S.; Garcia, R. R.; Olivero, J. J.; Bevilacqua, R. M.; Schwartz, P. R.; Clancy, R. T.; Muhleman, D. O. (American Meteorological Society, 1985)
Two-dimensional model calculations of the photochemistry and transport of carbon monoxide in the stratosphere, mesosphere, and lower thermosphere are presented. Results are compared to available observations at midlatitudes, where both observation and theory suggest that mesospheric CO abundances are larger on average in winter than in summer. The calculations also indicate that extremely large densities of CO should be found in the polar night mesosphere and upper stratosphere, but at present no high-latitude data are available for direct comparison. However, it is suggested that such a latitudinal distribution implies that the midlatitude region can exhibit unusually large abundances of CO under conditions of large-scale planetary wave activity. Two midlatitude observations during late January 1982 am shown to be consistent with this possibility.